2005
DOI: 10.1007/s00066-005-1242-9
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Trial of Simultaneous Whole-Brain Irradiation and Dose-Escalating Topotecan for Brain Metastases

Abstract: For a daily topotecan schedule simultaneous to WBRT, the maximum tolerated dose is 12 x 0.5 mg/m(2) in chemonaïve patients. For chemo-pretreated patients, daily doses should be reduced to 0.4 mg/m(2). A phase III trial has now been started to find out whether WBRT + topotecan increases survival compared to WBRT alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…Compared with our own previous data generated in a phase I/II study, where we found overall response rates of 72% (Hedde et al, 2007), the outcome of the patients treated with a combined approach was inferior. However, our results confirm the findings of the only two comparable studies testing a topotecan-based radiochemotherapy, in which overall response rates of 46 and 58%, respectively, were described (Gruschow et al, 2002;Kocher et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Compared with our own previous data generated in a phase I/II study, where we found overall response rates of 72% (Hedde et al, 2007), the outcome of the patients treated with a combined approach was inferior. However, our results confirm the findings of the only two comparable studies testing a topotecan-based radiochemotherapy, in which overall response rates of 46 and 58%, respectively, were described (Gruschow et al, 2002;Kocher et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…As a consequence, three phase I/II-studies were initiated to evaluate the feasibility of topotecan-based combined radiochemotherapy in patients with brain metastases (Gruschow et al, 2002;Kocher et al, 2005;Hedde et al, 2007). In the setting of the doseescalating phase I studies, Gruschow et al (2002) and Hedde et al (2007) found tolerable toxicities in those patients receiving 0.4 mg m À2 day À1 topotecan, either as a bolus or continuous infusion, concurrent with the WBRT (fraction size of 2 Gy day À1 for a total of 40 Gy).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Two retrospective trials examined the outcomes of multiple treatments including WBRT, surgery, chemotherapy, or supportive care 42,43 . Twelve studies examined the use of various WBRT dose fractionation schedules 6,10,22,28,[44][45][46][47][48][49][50][51] , and seven trials assessed the efficacy of radiosensitizers and WBRT as compared with WBRT alone 9,21,24,25,[52][53][54] . Chemotherapy and WBRT were compared in eight studies 7,8,[55][56][57][58][59][60] .…”
Section: Multiple Brain Metastasesmentioning
confidence: 99%